Effect of Dietary Incorporation of Short Chain and Medium Chain Fatty Acid on Feed Intake and Serum metabolites in Broiler Chickens - Gantayat, Banani; Durge, S.M.; Amrutkar, S.A.; Dongre, V.B. (Indian Journal of Animal Nutrition, 2020)
An experiment was conducted to study the effect of incorporation of short chain and medium chain fatty acid (SCMCFA) on feed intake and serum parameters in broiler chickens. Three hundred one-day-old AP-95 strain broiler chicks were reared under uniform managemental conditions. The broiler chicks were individually weighed and distributed randomly into five treatments having four replicates with 15 birds per replicate. The treatments were fed control diets (C), control plus probiotics (500 mg/kg; P), control plus SCMCFA (1000 mg/kg; F), control plus butyric acid supplement (500 mg/kg; B) and control plus SCMCFA + butyric acid (1000 mg/kg + 500 mg/kg; FB) in starter, grower and finisher diets. The intake followed similar trend in all the groups during the six-week study period, except a significant decline in feed intake in the probiotic group in the fifth week. The groups supplemented with SCMCFA showed normal values favouring intake. In case of blood glucose, cholesterol and serum triglycerides, similar values were observed among the different groups. These results indicated that dietary supplementation of SCMCFA positively influenced feed intake, blood glucose, cholesterol and triglycerides values in broiler chicken